Women's preferences for contralateral prophylactic mastectomy: An investigation using protection motivation theory. Issue 5 (May 2016) - Tesson, Stephanie; Richards, Imogen; Porter, David; Phillips, Kelly-Anne; Rankin, Nicole; Musiello, Toni; Marven, Michelle; Butow, Phyllis
Highlights: Breast cancer survivors choose contralateral prophylactic mastectomy for numerous reasons. Psychological, cosmetic and emotional motives influence decision-making. Perceived survival benefit and overestimated life-threat are also influential. Tailored patient counselling is needed to accurately convey risk. Educational materials are warranted to communicate CPM's benefits and risks. Abstract: Objective: Most women diagnosed with unilateral breast cancer without BRCA1 or BRCA2 mutations are at low risk of contralateral breast cancer. Contralateral Prophylactic Mastectomy (CPM) decreases the relative risk of contralateral breast cancer, but may not increase life expectancy; yet international uptake is increasing. This study applied protection motivation theory (PMT) to determine factors associated with women's intentions to undergo CPM. Methods: Three hundred eighty-eight women previously diagnosed with unilateral breast cancer and of negative or unknown BRCA1 or BRCA2 status were recruited from an advocacy group's research database. Participants completed measures of PMT constructs based on a common hypothetical CPM decision-making scenario. Results: PMT constructs explained 16% of variance in intentions to undergo CPM. Response efficacy (CPM's advantages) and response costs (CPM's disadvantages) were unique individual predictors of intentions. Conclusion: Decision-making appears driven by considerations of the psychological, cosmetic and emotional advantages and disadvantages of CPM. Overestimations of threat to life from contralateral breast cancer and survival benefit from CPM also appear influential factors. Practice implications: Patients require balanced and medically accurate information regarding the pros and cons of CPM, survival rates, and recurrence risks to ensure realistic and informed decision-making.